2009
DOI: 10.1007/s10646-009-0323-4
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ether flame retardants in eggs may reduce reproductive success of ospreys in Oregon and Washington, USA

Abstract: Spatial and temporal assessments and reports of polybrominated diphenyl ether (PBDE) flame retardants in birds remain sparse. In the present study, PBDEs were detected in all 120 osprey (Pandion haliaetus) eggs collected. The eggs were collected from nests along the Columbia, Willamette and Yakima rivers of Oregon (OR) and Washington (WA) and in Puget Sound (WA) between 2002 and 2007. PBDE congeners: 17, 28, 47, 49, 66, 85, 99, 100, 138, 153, 154 (possible coelution with brominated biphenyl 153 [BB153]), 183, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 35 publications
3
52
5
Order By: Relevance
“…1). Results from contaminant studies using passive samplers, fish tissues, and osprey eggs in 2008-2010(Henny et al, 2009Alvarez et al, 2014-in this issue;Christiansen et al, 2014-in this issue;Nilsen et al, in this issue;Torres et al, in this issue) were used to help select these three study reaches. Sample reaches were made approximately 16 km in length and were located to encompass sampling sites for largescale suckers (Nilsen et al, 2014-in this issue), osprey eggs (Henny et al, 2011), and passive contaminant samplers (Alvarez et al, in this issue).…”
Section: Study Areamentioning
confidence: 99%
“…1). Results from contaminant studies using passive samplers, fish tissues, and osprey eggs in 2008-2010(Henny et al, 2009Alvarez et al, 2014-in this issue;Christiansen et al, 2014-in this issue;Nilsen et al, in this issue;Torres et al, in this issue) were used to help select these three study reaches. Sample reaches were made approximately 16 km in length and were located to encompass sampling sites for largescale suckers (Nilsen et al, 2014-in this issue), osprey eggs (Henny et al, 2011), and passive contaminant samplers (Alvarez et al, in this issue).…”
Section: Study Areamentioning
confidence: 99%
“…Van den Steen et al [89] observed negative effects of PBDEs on reproductive performance in European starlings. A field study in the US [90] reported a negative relationship between reproductive performance and PBDEs in eggs of wild ospreys at two locations in the highly contaminated Columbia River valley of Oregon and Washington. North American osprey populations may be at risk for contaminant-induced reproductive impairment.…”
Section: Birdsmentioning
confidence: 99%
“…These chemicals inhibited osprey reproduction in terms of young produced per nest and concentrations in eggs increased rapidly, with the highest concentrations in downstream areas (Henny et al, 2009(Henny et al, , 2011. Flame retardant chemicals are widespread in the LCR and in juvenile salmon tissues, especially near urban and industrial areas (LCREP, 2007).…”
Section: Introductionmentioning
confidence: 99%